The Constructive Uses of Aeroelasticity - Ashley, H.; Lehman, L.L.; Nathman, J.K. (Engineering Transactions, 1982)
Dedicated to Professor Władysław Piszdon on the occasion of his seventieth birthday Historical, previously-published and new material is illustrated and discussed in support of the proposition that static or dynamic structural deformations of aerospace vehicles can often be used for constructive purposes. Examples are presented chronologically in categories related to the intended function. Efficient control of flight is attainable, as by the Wrights’ wing warping. Constraints can be relaxed on the performance of high-speed aircraft, fixed-pithc propellers and rotors. Accelerations and loads in rough air are diminished. Aeroelastic deformations furnish a means for primary propulsion. Prospects for the future are examined, notably the "complete aeroelastic CCV".